Spread beyond the border: Small Scale genetic structure of the introduced Banggai cardinalfish (Pterapogon kauderni) population in the Bali Strait - I Nyoman Giri Putra; Ni Luh Putu Ria Puspitha; Endang Wulandari Suryaningtyas (Marine Science Department Diponegoro University, 2021)
The living marine aquarium trade has been known to mediate various aquatic invaders to spread and established a new population outside of their natural home range. In most cases, the introduce species cause a cascaded effect which harm the native species and their ecosystem. The successful of the invasion event often related to the genetic properties of the introduced species. Therefore, using a molecular approach based on a mitochondrial DNA marker, the present work aimed to evaluate the population genetic structure of the introduced P. kauderni population in Bali Strait. Samples were collected from four sites in Gilimanuk Bay, Bali Strait. Our results showed a high haplotype diversity and low nucleotide diversity that might be a signal of a bottleneck. Overall, we found five haplotypes comprising two unique haplotypes and three shared haplotypes. Genetic structure was detected in some localities, which indicates Pterapogon kauderni might originated from various genetically distinct populations. However, we could not conclusively determine the observed patterns of the genetic structure within each site. These patterns are likely related to the multiple introduction event of P. kauderni in Bali Strait. Additional samples from both side (introduced and native habitat) combined with more rapidly evolving markers may describe the structure more clearly.